Comparing the Research Contributions of Community Pharmacy Foundation Funding on Practice Innovation Between Non-Academics and Academics - Anthony W Olson; Brian Isetts; Anne Marie Kondic; Jon Schommer (University of Minnesota Libraries Publishing, 2017)
Objective: Evaluate and compare the research contributions of Community Pharmacy Foundation (CPF) funding on community pharmacy practice innovation between non-academic and academic principal investigators (PIs) with respect to the following measurements: 1) "Pharmacy Practice Activity Classifications" (PPAC); 2) CPF "Coordinated Use of Medications"; and 3) CPF Investigator Impact. Methods: Quantitative data for all 124 CPF-funded grants awarded from 2002-2016 were obtained from the CPF website and personnel, while ethnographic qualitative data was generated from queries of PIs. Grant categorization was conducted by researchers serving as judges trained on the rules and procedures for coding. A threshold level of 90% agreement in scores of independent judging was established a priori. Findings were summarized and groups were compared using descriptive statistics for quantitative data and a thematic analysis of PI ethnographic reflections for qualitative data. Results: There were no differences between non-academic and academic PI groups for Coordinated Use of Medications and PPAC domains, but non-academics contributed more to two dispensing-related PPAC subclasses: 'Preparing the Product' (10% vs. 2%) and 'Delivering the Medication or Device' (13% vs. 2%). Analysis of investigator reflections revealed similarities between groups regarding impact on practice innovations, expanded collaborations, new practice tools, and patient-care financing models. Conclusions: CPF funding contributed new knowledge and resources for expanding and enhancing practice innovations as shown by quantitative (PPAC & Coordinated Use of Medications) and qualitative (PI impact) measures. Similarities between PI groups suggest that the CPF has established a funding niche with unique diversity of practice innovation opportunities. This investigation's findings may be useful to the CPF's continuous quality improvement efforts, as well as future grant applicants to assess research gaps in the medication use process and develop sustainable, transferable, and replicable patient-care innovations in community pharmacy practice. Conflict of Interest This program evaluation analysis was funded by the Community Pharmacy Foundation (CPF). Co-author Anne Marie Kondic is Executive Director and Grants Administrator for the Community Pharmacy Foundation. The ideas articulated in the manuscript are those of the authors to characterize historical CPF grant funding and do not necessarily indicate or impact future funding priorities.   Type: Original Research